2021
DOI: 10.3390/ijms22169074
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Skewed X-Chromosome Inactivation in Female Hemophilia Patients—Lessons from Wide Genome Analyses

Abstract: Introduction: Hemophilia A (HA) is an X-linked bleeding disorder caused by factor VIII (FVIII) deficiency or dysfunction due to F8 gene mutations. HA carriers are usually asymptomatic because their FVIII levels correspond to approximately half of the concentration found in healthy individuals. However, in rare cases, a carrier may exhibit symptoms of moderate to severe HA primarily due to skewed inactivation of her non-hemophilic X chromosome. Aim: The aim of the study was to investigate X-chromosome inactivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…[13–15] Recently, some reports revealed that XCI might be a modifier of FVIII plasma levels, leading to the low expression of clotting factor levels and bleeding symptoms in HA carriers. [16–18] Correlation between XCI patterns and FVIII levels in HA female carriers with the same F8 variant contributed to further confirm this theory. In this study, we reported a novel variant in the F8 (NM_000132.4): c.6193T > G (p.W2065G) gene in a Chinese HA family.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…[13–15] Recently, some reports revealed that XCI might be a modifier of FVIII plasma levels, leading to the low expression of clotting factor levels and bleeding symptoms in HA carriers. [16–18] Correlation between XCI patterns and FVIII levels in HA female carriers with the same F8 variant contributed to further confirm this theory. In this study, we reported a novel variant in the F8 (NM_000132.4): c.6193T > G (p.W2065G) gene in a Chinese HA family.…”
Section: Introductionmentioning
confidence: 63%
“…[8][9][10] 46, XX female is a mosaic of 2 cell types that expresses both maternal and paternal X chromosomes. Normally, cells have equal inactivation (50:50) of the maternal or paternal X chromosome, but some females have preferential inactivation of 1 X chromosome, which is known as skewed X-chromosome Zhang et al • Medicine (2023) 102: 18 Medicine inactivation (XCI). [11,12] In females, skewed XCI can result in phenotypic heterogeneity of many X-linked disorders, disease severities were positive correlation with the activated ratio of mutated X chromosome.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying this skewed choice towards inactivating the chromosome harboring the normal allele have not been elucidated yet. It has recently been described that additional deleterious mutations on the other X-chromosome may favor the negative selection of cells in which it is expressed, generating skewed XCI and contributing to the expression of a given phenotype [19]. However, such a mechanism was not identified in the proband.…”
Section: Discussionmentioning
confidence: 99%
“…Skewed X-chromosome inactivation can be seen in the general population [17], with levels of skewing increasing with age [18], as it may have been the case for the proposita's mother. However, it is also a common feature in symptomatic carriers of X-linked mutations, favoring the expression of the mutated allele [19,20], which is the case of the proband.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to conventional assays to analyze coagulation function, a combination of genetic analyses (e.g., chromosomal complement, molecular genetic examinations (e.g., mutational screening of the causative genes), XCI assay, linkage analysis) is required to explicit the underlying mechanism in female hemophilia, especially when only one mutation is detected. Notably, a recent study for heterozygous female HA patients indicated that the main reason for skewed XCI in patients was negative selection against cells with a disadvantage caused by an additional deleterious mutation in hemophilia-unrelated genes on the silenced X chromosome (i.e., the X chromosome without the HA mutation) [ 36 ]. If the hypothesis is true, the two X chromosomes of affected females will be expected to be either homozygous or compound heterozygous for hemophilia mutations, or have a hemophilia mutation in one X chromosome combined with a deleterious mutation in hemophilia-unrelated genes on the other X chromosome that will render preimplantation genetic testing infeasible.…”
Section: Discussionmentioning
confidence: 99%